2013
DOI: 10.1089/end.2012.0408
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Restrictive Bariatric Surgery on Urolithiasis

Abstract: Questions remain whether purely restrictive bariatric procedures such as sleeve gastrectomy or adjustable gastric banding avoid the risk of kidney stones. Our study demonstrates a very low incidence of kidney stones after restrictive bariatric procedures, although larger sample sizes, longer follow-up times, and controlled prospective studies are necessary to validate this finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 13 publications
0
38
0
Order By: Relevance
“…[4][5][6] RYGB increases urinary oxalate excretion and decreases urinary citrate, conditions commonly associated with the development of calcium oxalate stones. [7][8][9] Indeed, calcium oxalate stones comprise 75% to 80% of all stones in RYGB patients, implicating hyperoxaluria in the pathogenesis of urolithiasis.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] RYGB increases urinary oxalate excretion and decreases urinary citrate, conditions commonly associated with the development of calcium oxalate stones. [7][8][9] Indeed, calcium oxalate stones comprise 75% to 80% of all stones in RYGB patients, implicating hyperoxaluria in the pathogenesis of urolithiasis.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent data suggest that modern bariatric procedures, such as Roux-en-Y bypass, may also impart a twofold increased risk of nephrolithiasis, while 20-75% may have hyperoxaluria, including 20% with very high urine oxalate levels, also putting them at considerable risk of oxalate nephropathy (Table 2) (2,(5)(6)(7)(8)(9)(10)(11)(12). Purely restrictive bariatric procedures, such as gastric banding, may not increase oxalate excretion, yet more data are needed (Table 2) (13)(14)(15)(16). Morbidly obese patients are increasingly encouraged to consider bariatric surgery in order to meet body mass index thresholds for renal or other solid-organ transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…Restrictive procedures (LAGB and SG) had a much lower stone incidence rate of 1.3% (8/618) compared with obese controls 4.6% (258/5569) during a similar 2-year time frame. 35,36 The literature on the incidence of nephrolithiasis after RYGB consists of only a small sample of studies and more efforts are needed to delineate direct causation. Matlaga et al presented the first large-scale claims data report in a casecontrol study of 4639 patients in which they found a 7.65% incidence of urolithiasis in post-RYGB patients versus 4.63% in obese patients in the control group ( p < 0.0001).…”
Section: Resultsmentioning
confidence: 99%
“…Although taken from a small sample, the combined risk of 1.3% (n = 618) appears to be lower than the risk present in obese control individuals of 4.6% (n = 5569). 35,36 Strategies, limitations, and solutions to reduce calcium oxalate stone risk after RYGB Largely, the key strategies to prevent kidney stones after bariatric surgery are similar to those recommended to all stone formers and a summary is provided in Table 2. As discussed above, low urine volume status in bariatric surgical patients can significantly increase the risk of nephrolithiasis due to supersaturation of stone-forming solute particles.…”
Section: Resultsmentioning
confidence: 99%